Teachers’ Perceptions about the Use of Code-Mixing in Teaching English - Sri Wahyuni; Nur Aeni; Hasriani G; Nur Aeni (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2023)
This study aims to determine the perceptions of the teachers about the use of code-mixing in teaching English. The researchers used a mixed-method triangulation research design (quantitative-qualitative). To achieve the research objectives, the data collected is the result of observation, interview, and questionnaire. The sample in this research was the teacher who taught in a third-year English class in SMP 4 Bantimurung. The results of data analysis showed that the perceptions of teachers had positive perceptions about the use of code-mixing in teaching English as evidenced by the results of observations and interviews which showed positive responses to the use of code-mixing and also supported by accurate data from a questionnaire where there was mean score 68 for teacher. The reason why a teacher had a positive perception of code mixing in teaching English is that the teacher considers that code-mixing can help teachers to make students more actively participate in taking English lessons. The use of L1 or Indonesian by the teacher can help students understand teacher instructions, subject matter, assignments, and even exams. In addition, students can also improve their vocabulary and how to pronounce new vocabulary acquired during the teaching-learning process.